Guiding postmenopausal care for osteoporosis: First evidence-based clinical practice guidelines for Pakistan - Pervez, Alina; Chandran, Manju; Khan, Aysha Habib (Journal of the Pakistan Medical Association, 2024)
Madam, We would like to address the issue of postmenopausal osteoporosis (PMO) management in Pakistan and advocate for the country-wide dissemination of the recently published Pakistan-specific clinical practice guideline (CPG) "GRADE-Adolopment of Clinical Practice Guideline for Postmenopausal Osteoporosis Management - a Pakistani Context" (1). Osteoporosis poses a significant threat to the health of postmenopausal women. Although osteoporosis prevalence among postmenopausal women ranges from 20% to 49.3% in Pakistan, there is a lack of epidemiological data, diagnostic facilities, and public awareness about bone health. Healthcare providers in Pakistan have thus far struggled with managing osteoporosis effectively because of the absence of local CPGs. The Pakistani PMO guideline, developed by the Aga Khan University aligns the recommendations of the Asia Pacific Consortium on Osteoporosis (2) and the American Association of Clinical Endocrinologists (3). The GRADE-ADOLOPMENT methodology used in developing the guideline provides a systematic support for the recommendations that are evidence based and suitable for adoption in Pakistan's medical settings. The guideline recommends higher doses (2000-4000 IU) of vitamin D in patients with obesity, malabsorption, and old age, considering their increased requirements and suboptimal response to lower doses. It addresses food insecurity and malnutrition, which contribute to vitamin D deficiency and fracture risk. Moreover, the guideline incorporates the surrogate FRAX model created for Pakistan, recommended by the International Osteoporosis Foundation for countries lacking fracture incidence data (4). A management algorithm is proposed, based on intervention thresholds developed for Pakistan for accurate estimation of fracture probability, and to guide clinical practice(5). The primary goal of the guideline is to improve the quality of care by changing the daily practice of physicians in the desired direction. Disseminating and integrating osteoporosis care into the healthcare system is challenging but remains a top priority. The endorsement of the guideline by relevant national societies can play a crucial role in its dissemination. Implementation through their members can help in assessing effectiveness and in shaping clinical practice. The guideline is a critical step in addressing osteoporosis management challenges in Pakistan, but for full impact, widespread dissemination and implementation in clinical practice is required. We implore the medical community, policymakers, and stakeholders to collaborate in this endeavor and work towards improving the management of osteoporosis, to enhance the health outcomes of the Pakistani population. It is essential that healthcare policymakers and practitioners recognize PMO as a significant public health issue and implement the CPG for appropriate practice changes.